Aspek Keamanan dan Perlindungan Data Rekam Medis Elektronik di Puskesmas Sungai Mesa Banjarmasin - Anshari, Muhammad Rashif; Yunita, Nirma; Noor, Fatmawati Bakti; Noviani, Nurul (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Electronic Medical Records are implemented to ensure the security, confidentiality, integrity, and availability of data in accordance with data and information security principles. This study aims to explore the security and data protection aspects of EMR at Sungai Mesa Public Health Center in Banjarmasin. This is a qualitative research with a case study design, using interviews and observations. The subjects consisted of four individuals: the Head of the Health Center, a Doctor, and Registration Officers. The results show that confidentiality is ensured through login systems with personal usernames and regularly updated passwords, with access restricted based on roles. Integrity is maintained through the "Edit" feature, allowing data modification according to authority. Availability is supported by the "Search" feature, though there are obstacles such as internet disruptions, power outages, and the absence of an independent backup system. Legally, there are SOPs on data misuse sanctions, but no training or socialization has been conducted. In conclusion, confidentiality and integrity are well-implemented, while availability still faces technical challenges.